2015
DOI: 10.1037/bne0000098
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity in hippocampal cells related to the facilitative effect of intracranial self-stimulation on a spatial memory task.

Abstract: Posttraining intracranial self-stimulation (SS) in the lateral hypothalamus facilitates the acquisition and retention of several implicit and explicit memory tasks. Here, intracellular injections of Lucifer yellow were used to assess morphological changes in hippocampal neurons that might be specifically related to the facilitative posttraining SS effect upon the acquisition and retention of a distributed spatial task in the Morris water maze. We examined the structure, size and branching complexity of cornus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…The electrical activation of the medial forebrain bundle (MFB) via Intracranial self-stimulation (ICSS) has been confirmed in our and other laboratories as a treatment capable of consistently facilitating the acquisition and retention in a wide array of experimental paradigms, for both implicit [1], [2], [3], [4] and explicit memory [5], [6], in rats. Several mechanisms of action have been proposed to explain these facilitating effects of ICSS on learning and memory.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The electrical activation of the medial forebrain bundle (MFB) via Intracranial self-stimulation (ICSS) has been confirmed in our and other laboratories as a treatment capable of consistently facilitating the acquisition and retention in a wide array of experimental paradigms, for both implicit [1], [2], [3], [4] and explicit memory [5], [6], in rats. Several mechanisms of action have been proposed to explain these facilitating effects of ICSS on learning and memory.…”
Section: Introductionmentioning
confidence: 90%
“…Learning and memory facilitation has also been linked to structural plasticity induced by ICSS [11]. Recent work undertaken in our laboratory has shown an increase in the density of dendrite spines in the CA1 neurons of the hippocampus in rats that received ICSS after training in a spatial task [6]. These morphological modifications could be related to changes in the expression of several plasticity-related genes caused by the posttraining ICSS treatment, with increased levels of Nurr1, c-Fos and Arc protein consistently being found in hippocampus, amygdala, dorsal striatum, lateral hypothalamus or retrosplenial cortex [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…This was done in a single session of 2500 self-administered trains of stimulant current at each particular OI using the same Skinner box where ICSS behavior had been established. The parameters of the stimulation in terms of frequency, intensity and number of trains administered were the same as previous studies since it has been shown to effectively enhance memory, both implicit [ 33 35 ] and explicit [ 6 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of ICSS in animals allows us to unequivocally ensure that stimulation activates the reward system in a functional manner. In a similar way to F-DBS, ICSS of the LH has a reliable enhancing effect on hippocampus-dependent explicit memory [ 6 8 ]. However, while F-DBS affects fornix fibers, ICSS of the LH activates the MFB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation